Kings and philosophers, 1689-1789 - Krieger, Leonard (The Norton history of modern Europe, 1970)
The kings, 1689-1748. The nature of kingship ; The kings at war, 1688-1721 ; The kings at home : the old powers, 1689-1748 ; The kings at home : the ascending powers, 1714-1748 -- The philosophers, 1687-1789. The social context ; The worldly philosophers, 1687-1776 ; The unworldly philosophers, 1770-1789 -- The philosopher kings. Enlightened absolutism ; The enlightened absolutists abroad ; The enlightened absolutists at home ; The end of an era : the social movement in the West, 1763-1789.